Experiences from Garbha-Swasthya helpline - Koumudi G Godbole; Shilpa S Kulkarni; Girish P Godbole; Aparna M Kulkarni (Wolters Kluwer Medknow Publications, 2015)
Garbha-Swasthya helpline is a telephone helpline run by a tertiary care private hospital to address issues related to pregnancy and its complications. A review of the helpline data from September 2010 to December 2012 was conducted to study caller characteristics, number of calls and related information, and the reasons to call. Out of the total 696 voice calls, 421 were new callers and 275 were repeat callers and they comprised mainly pregnant women (73.3%), their relatives (24.8%), and medical professionals (1.9%). Most calls were related to first pregnancy and were mainly from Pune and other cities of Maharashtra. All calls by the medical professionals were regarding drug safety in pregnancy. The commonest category of questions (27.4%) was about exposures (drugs, alcohol, eclipse, radiation, etc.) and preexisting medical illness followed by pregnancy complications (18.5%), common medical issues such as nausea/vomiting during pregnancy, and delivery and postpartum period (14% each). Although the total number of calls received has steadily increased, efforts to create public and professional awareness to increase the usage of this helpline are warranted.